Nonhematopoietic Peroxisome Proliferator–Activated Receptor-α Protects Against Cardiac Injury and Enhances Survival in Experimental Polymicrobial Sepsis*. Issue 8 (August 2016) - Standage, Stephen W.; Waworuntu, Rachel L.; Delaney, Martha A.; Maskal, Sara M.; Bennion, Brock G.; Duffield, Jeremy S.; Parks, William C.; Liles, W. Conrad; McGuire, John K.
Abstract : Objectives: Peroxisome proliferator–activated receptor-α is significantly down-regulated in circulating leukocytes from children with sepsis. Peroxisome proliferator–activated receptor-α null ( Ppara -/- ) mice have greater mortality than wild-type mice when subjected to sepsis by cecal ligation and puncture. We sought to characterize the role of peroxisome proliferator–activated receptor-α in sepsis and to identify the mechanism whereby peroxisome proliferator–activated receptor-α confers a survival advantage. Design: Prospective randomized preclinical study. Setting: Laboratory investigation. Subjects: Male C57Bl/6J and Ppara –/– mice (B6.129S4-Ppara tm1Gonz /J), aged 12–16 weeks. Interventions: Bone marrow chimeric mice were generated and subjected to cecal ligation and puncture. Survival was measured for 7 days. Separate groups of nontransplanted mice underwent cecal ligation and puncture and were euthanized 24 hours later for plasma and tissue analyses. Measurements and Main Results: Ppara -/- mice had dramatically reduced survival compared with wild-type mice irrespective of the peroxisome proliferator–activated receptor-α status of the bone marrow they received (3% vs 63%; p < 0.0001). No difference in survival was observed between Ppara -/- mice that received wild-type versus Ppara -/- marrow or in wild-type mice receiving wild-type versus Ppara -/- marrow. In septic, nontransplanted mice at 24 hours, Ppara -/- mice had elevated cardiac troponin levels compared with wild-type mice. Cardiac histologic injury scores were greater in Ppara -/- versus wild-type mice. Expression of transcription factors and enzymes related to fatty acid oxidation in the heart were profoundly down-regulated in both wild-type and Ppara -/- mice, but more so in the Ppara -/- mice. Conclusions: Peroxisome proliferator–activated receptor-α expression in nonhematopoietic tissues plays a critical role in determining clinical outcome in experimental polymicrobial sepsis and is more important to survival in sepsis than hematopoietic peroxisome proliferator–activated receptor-α expression. Cardiac injury due to inadequate energy production from fatty acid substrate is a probable mechanism of decreased survival in Ppara -/- mice. These results suggest that altered peroxisome proliferator–activated receptor-α–mediated cellular metabolism may play an important role in sepsis-related end-organ injury and dysfunction, especially in the heart. Abstract : Supplemental Digital Content is available in the text.